Inflation in Emerging and Developing Economies : Evolution, Drivers and Policies - Ha, Jongrim; Kose, M. Ayhan; Ohnsorge, Franziska (Washington, DC: World Bank, 2018)
Emerging market and developing economies, like advanced economies, have experienced a remarkable decline in inflation over the past half-century. Yet, research into this development has focused almost exclusively on advanced economies. This book fills that gap, providing the first comprehensive and systematic analysis of inflation in emerging market and developing economies. It examines how inflation has evolved and become synchronized among economies; what drives inflation globally and domestically; where inflation expectations have become better-anchored; and how exchange rate fluctuations can pass through to inflation. To reach its conclusions, the book employs cutting edge empirical approaches. It also offers a rich data set of multiple measures of inflation for a virtually global sample of countries over a half-century to spur further research into this important topic.